The baptism of the Holy Spirit the views of A.B. Simpson and his contemporaries - Gilbertson, Richard; Christian and Missionary Alliance (Camp Hill, PA Christian Publications, 1993)
Includes bibliographical references.
Originally written as a Masters thesis under Dr J.I. Packer. Winner of the Pardington Prize.
Keywords: Simpson, A.B., -- (Albert Benjamin), -- 1844-1919.; Baptism of the Holy Spirit -- Biblical teaching